Aptamer-based impedimetric determination of the human blood clotting factor IX in serum using an interdigitated electrode modified with a ZnO nanolayer - Cheen, O.C.; Gopinath, S.C.B.; Perumal, V.; Arshad, M.K.M.; Lakshmipriya, T.; Chen, Y.; Haarindraprasad, R.; Rao, B.S.; Hashim, U.; Pandian, K. (Springer Verlag (Germany), 2017)
This article describes a sensitive impedimetric method for the determination of human blood coagulation factor IX protein (FIX) which is present in extremely low concentration in serum. An interdigitated electrode (IDE) whose surface was layered with zinc oxide was modified with two kinds of probes. One is an antibody, the other an aptamer against FIX. A comparative study between anti-FIX aptamer and anti-FIX antibody showed the aptamer to possess higher affinity for FIX. A sandwich aptamer assay was worked out by using the FIX-binding aptamer on the surface of the IDE. It has a detection limit as low as 10 pM which makes it 4 to 30-fold more sensitive than any other method reported for FIX. Moreover, to practice detection in clinical samples, FIX was detected from the human blood serum by spiking. In our perception, the sensitivity of the ZnO-modified IDE presented here makes it a promising tool for sensing clinically relevant analytes that are present in very low (sub-pM) concentrations.